Digital technologies and leadership practices in Greek elementary schools - Kokkonos, Antonios; Travlos, Antonios; Antonopoulou, Panagiota; Pavlis Korres, Maria; Choustoulakis, Emmanouil (International Journal of Evaluation and Research in Education (IJERE), 2025)
The rapid advancement and widespread adoption of digital technologies have significant implications for leadership theory and practice, which remain largely unexplored in the current literature. This study investigates how demographic characteristics influence the perceptions of elementary school principals and educational staff regarding the digital age and leadership practices. Employing a quantitative research approach, data were collected through a web survey based on the questionnaire for digital technologies and leadership practices (QDTLP) from 505 participants in 215 elementary schools of Peloponnese Region. Multivariate analysis of variance (MANOVA) and univariate analysis of variance (ANOVA) were employed to examine differences in perceptions based on gender, age, education level, subject specialization, years of teaching experience, years of work at the current school, role in the school, and the Directorate of Primary Education (DPE) the school belongs to. The findings indicate that age, education level, years of teaching experience, and role in the school significantly affect perceptions, while gender, subject specialization, and DPE the school belongs to, do not demonstrate a significant influence. The study provides valuable insights into how demographic characteristics shape perceptions about digital technologies and leadership within the elementary school context, contributing to the adaptation of leadership practice in the digital age.